2013
DOI: 10.5713/ajas.2012.12563
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of <italic>Longissimus</italic> and <italic>Semitendinosus</italic> Muscles from Beef Cattle Subjected to Non-penetrative and Penetrative Percussive Stunning Methods

Abstract: This study provides a comparative analysis of the effects of pre-slaughter penetrative and non-penetrative stunning and post-slaughter stunning on meat quality attributes in longissimus lumborum (LL) and semitendinosus (ST) muscles in heifers. Ten animals were assigned to each of four treatment groups: i) animals were subjected to conventional Halal slaughter (a clean incision through the structures at the front of the upper neck - the trachea, oesophagus, carotid arteries and jugular veins) and post-cut penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…(Table 4). These results parallel previously conducted research on the impact of stun methods on cooking loss and Warner-Bratzler shear force for nonpenetrating or penetrating captive bolt stunned beef (Sazili et al, 2013). However, other investigators have identified significant differences in cooking loss and Warner-Bratzler shear force between unstunned, electrically stunned, and captive bolt stunned beef (Önenç and Kaya, 2004).…”
Section: Resultssupporting
confidence: 86%
“…(Table 4). These results parallel previously conducted research on the impact of stun methods on cooking loss and Warner-Bratzler shear force for nonpenetrating or penetrating captive bolt stunned beef (Sazili et al, 2013). However, other investigators have identified significant differences in cooking loss and Warner-Bratzler shear force between unstunned, electrically stunned, and captive bolt stunned beef (Önenç and Kaya, 2004).…”
Section: Resultssupporting
confidence: 86%
“…Shear force values for both treatments reduced with aging time. The improvement of tenderness in meat could be due to rigor resolution caused by the actions of the enzymes through the breakdown of collagen binding muscle fibers together under postmortem conditions Li et al, 2012;Sazili et al, 2013).…”
Section: Shear Force Valuesmentioning
confidence: 99%
“…; Anil ; Sazili et al . ; Nakyinsige et al . ,b), most works were conducted in poultry, sheep and cattle.…”
Section: Introductionmentioning
confidence: 99%